Avaliação da tutoria em um currículo médico : o discurso de estudantes de medicina - Luna, Willian Fernandes (2014)
This research aimed to evaluate the Tutorial Group on the model of Problem- Based Learning (PBL), inserted in a hybrid format of curriculum, using the speeches of medical students of Faculdade de Ciências Médicas da Paraíba. To understand the 16 theme-field we chose to develop a qualitative research. The theoretical and methodological references employed are authors who discuss the teaching-learning processes and language area and discourse analysis. As instruments the Conversation Circle techniques, field diary and observations were used.The Language repertoires were identified from their comments, focusing on the controversies of the speech, that formed seven sets of directions. We conclude that, from the speech of students, the insertion of Tutoring in formed the BPA in more traditional curricula can be an alternative to starting curricular change processes in the way of building a meaningful learning, provided there is consistent planning with the rest of curriculum. The methodological procedures used were the Conversation wheel techniques, field diary and observations. The Language repertoires were identified from their comments, focusing on the controversies of the discourse that formed seven sets of directions. It was concluded that, from the speech of students, the insertion of Tutorial in the PBL format in traditional curricula can be an alternative to starting curricular change processes in the way of building a meaningful learning, provided there is consistent planning with the rest of the curriculum.